The Effectiveness of Business Model Canvas (BMC) to Increase the Competitiveness of MSMEs in the Culinary Sector in Palopo City - Baso, Nurfatima Azzahra; Mahmut, Cici; Harla, Muh. Chaezar Fachreza (Amkop Management Accounting Review (AMAR), 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector contribute significantly to local economic growth in Palopo City. However, many MSME actors face challenges in sustaining their businesses due to the lack of systematic business strategies. This study aims to analyze the effectiveness of implementing the Business Model Canvas (BMC) in improving the performance of culinary MSMEs in Palopo. The research employed a quantitative approach by distributing questionnaires to 80 culinary MSME respondents, complemented by in-depth interviews to enrich the qualitative data. Data analysis was conducted using the Structural Equation Modeling (SEM) method to examine the influence of the nine BMC elements on competitiveness and business sustainability. The results indicate that Value Proposition, Customer Relationship, and Key Activities have a significant impact on revenue growth and customer loyalty. Meanwhile, Channels and Revenue Streams play an important role in expanding market access and enhancing profitability. These findings confirm that BMC is an effective strategic framework for strengthening the competitiveness of culinary MSMEs in Palopo and can serve as a reference for local governments and supporting institutions in formulating sustainable MSME development programs